2022
DOI: 10.1186/s42483-021-00106-w
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitination in the rice blast fungus Magnaporthe oryzae: from development and pathogenicity to stress responses

Abstract: Ubiquitination is a vital protein post-translational modification (PTM) prevalent in eukaryotes. This modification regulates multiple cellular processes through protein degradation mediated by the 26S proteasome or affecting protein–protein interaction and protein localization. Magnaporthe oryzae causes rice blast disease, which is one of the most devastating crop diseases worldwide. In M. oryzae, ubiquitination plays important roles in growth, pathogenicity, stress response and effector-mediated plant-pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…6). Notably, the deletion of MoEMC leads to the degradation of misfolded Atg9 by 26S proteasome pathway (Wang et al, 2022). Therefore, EMC is a direct modulator in autophagosome formation and is important for M. oryzae pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…6). Notably, the deletion of MoEMC leads to the degradation of misfolded Atg9 by 26S proteasome pathway (Wang et al, 2022). Therefore, EMC is a direct modulator in autophagosome formation and is important for M. oryzae pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…In M. oryzae , numerous signaling factors have been implicated in appressorium emergence and virulence [ 22 ]. M. oryzae would be a hemibiotrophic pathogen that goes through a biotrophic phase before transitioning to a necrotrophic phase which stimulates plant cell death [ 23 ].…”
Section: Autophagy In M Oryzaementioning
confidence: 99%
“…The functions of ubiquitination or ubiquitin-like modification have been widely revealed in both human fungal pathogens ( C. albicans and C. neoformans ) and plant fungal pathogens ( M. oryzae , Fusarium oxysporum, and Cryphonectria parasitica ) [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. In fungal pathogens, the role of ubiquitination has been studied by analyzing ubiquitin-related genes, and it was found that ubiquitination played important roles in fungal development, stress resistance, nutrient utilization, and fungal virulence [ 19 , 20 , 21 , 22 , 25 , 27 ].…”
Section: Biological Functions Of Dubs In Different Pathogenic Fungimentioning
confidence: 99%
“…Although the function of ubiquitination has been well revealed [ 17 , 18 ], deubiquitination mediated by DUBs has not been well summarized in pathogenic fungi. On the one hand, similar to ubiquitination, the biological functions of DUBs are quite different.…”
Section: Biological Functions Of Dubs In Different Pathogenic Fungimentioning
confidence: 99%